Hypertrophic obstructive cardiomyopathy: the Mayo Clinic experience - Kotkar, Kunal D. (Ann Cardiothorac Surg, 2017)
BACKGROUND: Hypertrophic cardiomyopathy (HCM) is a primary myocardial disease characterized by left ventricular hypertrophy in the absence of other etiologies. Clinical presentation may vary from asymptomatic to sudden cardiac death. Medical treatment is the first-line therapy for symptomatic patients. Extended left ventricular septal myectomy is the procedure of choice if medical treatment is unsuccessful or intolerable. MAYO CLINIC EXPERIENCE: More than 3,000 patients have had septal myectomy for HCM at the Mayo Clinic (MN, USA) from 1993 to 2016. Risk of hospital death after isolated septal myectomy for obstructive HCM is <1% and is similar to the risk of operation for elective mitral valve repair. Complications, such as complete heart block requiring permanent pacemaker, are uncommon (2%), although partial or complete left bundle branch block is a frequent finding on the postoperative ECG. Relief of left ventricular outflow tract (LVOT) obstruction with septal myectomy dramatically improves symptoms and exercise capacity in symptomatic patients with obstructive HCM. More than 90% of severely symptomatic patients have improvement by at least two functional classes, and reduction of outflow gradients by myectomy decreases or eliminates symptoms of dyspnea, angina and/or syncope. Basal obstruction with systolic anterior motion (SAM) is treated by transaortic myectomy. The transapical approach was applied in 115 patients with obstructive midventricular and apical variants of HCM between 1993 and 2012. All patients with midventricular obstruction had gradient relief and none developed an apical aneurysm or ventricular septal defect. Recurrent obstruction after satisfactory myectomy was rare. CONCLUSIONS: Septal myectomy effectively and definitively relieves LVOT obstruction and cardiac symptoms in patients with obstructive HCM. In experienced centers, early mortality for isolated septal myectomy is less than 1%, and overall results are excellent and continue to improve in the current era.